Postępowanie reprywatyzacyjne w Polsce - Wielgus, Kamil (Wydawnictwo Uniwersytetu Wrocławskiego, 2019)
In his paper, the author made an attempt at briefly presenting the issue of reprivatiza-tion in Poland and at proposing his own solution regarding this issue. Undoubtedly, this phenomenon is one of the many pathologies of post-communist countries. It is adifficult conflict of values between the interests of the collective and individual entities, both from the legal and axiological point of view. What is more, Poland is the only country that has not finally decided in favour of either side — in comparison to its geographical neighbours. The author proposes asolution to the issue of reprivatization based on prescription.
Keywords: reprivatization; procedure; agricultural reform; real properties in Warsaw